PENGGUNAAN STRUKTUR DAN UNSUR KEBAHASAAN DALAM TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 23 PADANG - Lestari, Devi Eva Riana Puji; Tressyalina, Tressyalina (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACTThis type of research is qualitative with descriptive methods. The data of this research are in the form of structure and linguistic elements from students' descriptions. The data source of this research is the description text of Grade VII students of SMP Negeri 23 Padang. The research instrument is the researcher himself. Data collection techniques through documentation study. The data collection technique in this research is the triangulation technique (Cross-Check). Data were analyzed by steps, (1) identifying common elements contained in the description text, (2) analyzing the text based on the aspects studied, namely the structure and linguistic elements of the description text, (3) the results of the analysis from the researcher were re-examined by the informant triangulation, (4) make conclusions. Based on the results of the study, the following three things were concluded. First, the structure of the text consists of the identification and description of parts. Identification / General description In the text description of the eighth grade students of SMP Negeri 23 Padang as a whole have been identified. Of the 35 data that have identification, there are 11 data that combine identification with the Description section. Next, the general description of the student's writing section is detailed. Evident from 35 texts that have a section description structure there are 14 texts whose description section consists of one paragraph and 1 text whose description of the section joins with identification. Second, in terms of language. The basic pattern of sentences that students use most often is SPK, while the sentence that is used most rarely is SPOPel. Third, the pattern of student reasoning that is most widely used is deductive reasoning. Of the 87 paragraphs there are 70 paragraphs using deductive reasoning, 2 paragraphs using inductive reasoning, and 15 paragraphs of incorrect reasoning patterns.Â Kata kunci:Struktur, Kalimat, Pola Penalaran Teks Deskripsi